Proceedings of the 10th International Conference on Computer Recognition Systems CORES 2017 - Kurzynski, Marek; Wozniak, Michal; Burduk, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book offers a comprehensive study of computer recognition systems - one of the most promising directions in artificial intelligence. It presents a collection of 52 carefully selected articles contributed by experts in the field of pattern recognition, discussing both methodological aspects and applications of current research. It includes the following sections: · Features, learning, and classifiers · Biometrics · Data stream classification and big data analytics · Image processing and computer vision · Medical applications · Applications It is a valuable reference tool for scientists dealing with the problems of designing computer pattern recognition systems, including researchers and students of computer science, artificial intelligence and robotics.
Recognition of Fuzzy or Incompletely Described Objects -- Evaluating and Comparing Classiﬁers: Review, Somem Recommendations and Limitations -- Multi-aspect Assessment and Classiﬁcation of Porous Materials Designed for Tissue Engineering -- Enhancing English-Japanese Translation Using Syntactic Pattern Recognition Methods -- Novel Results on Random Walk-Jump Chains that Possess Tree-based Transitions -- Travel Time Prediction for Trams in Warsaw -- Diagnostic Rule Extraction Using the Dempster-Shafer Theory Extended for Fuzzy Focal Elements -- Gait Recognition Using Motion Trajectory Analysis -- Methodology of the Construction of a GDPLL(k) Grammar-based Syntactic Pattern Recognition System -- Determining of an Estimate of the Equivalence Relation on the Basis of Pairwise Comparisons -- Classiﬁcation of Body Regions based on MRI Log Files -- Semi-automatic Segmentation of Scattered and Distributed Objects -- Playback Attack Detection: The Search for the Ultimate Set of Antispoof Features -- AVision-Based Method for Automatic Crack Detection in Railway Sleepers -- Towards Privacy-aware Keyboards.
Keywords: Computational intelligence; Artificial intelligence; Pattern recognition systems; Computational Intelligence; Artificial Intelligence; Automated Pattern Recognition